KAITAN TINGKAT PENDIDIKAN DENGAN KEPATUHAN MINUM OBAT PADA PASIEN TUBERKULOSIS (TB) PARU DI PUSKESMAS BOBOTSARI KABUPATEN PURBALINGGA - Siti Haniyah; Tophan Heri Wibowo; Iis Setiawan Mangku Negara (Universitas Harapan Bangsa Purwokerto, 2012)
Tuberculosis (TB) is a lower respiratory tract infection caused by theMicrobacterium tuberculosis. Pulmonary tuberculosis is the second leading causeof death in Indonesia. Pulmonary TB cases in the province of Central Java todayreached 6546 people, one of the districs where the incidence and mortality of TBis high, ie Purbalingga. Compliance patients in taking medication greatly affectthe patient’s recovery. According to Heriyono’s research at 2004, several factorsrelated to medication adherence pulmonary tuberculosis patients is education,knowledge, attitudes, employment, income and supervisory support to takemedication (PMO). This study aims to determine the relationship between theeducational level with adherence of medication in patients with pulmonarytuberculosis in Bobotsari Public Health Purbalingga. This research metod usingdescriptive quantitative research with cross sectional approach. The population inthis study were all patients with pulmonary TB were undergoing treatment at theBobotsari Health Public Purbalingga totaling 37 patients. The sample used for allpopulations in accordance with the inclucion and exclusion criteria.Questionnaires was used to collecting data of the research. There is arelationship between level of education and medication adherence in patients withpulmonary tuberculosis (TB) in the region of Bobotsari Health PublicPurbalingga (p=0.000). Keywords : level of education, compliance, pulmonary TB